The Impact of Social Media in Promoting Healthy Behaviors Among Hajj Pilgrims in Saudi Arabia. - Victoria-Mas, Juan Salvador; De-Aguilera-Moyano, Miguel; Alwajaan, Saud (CGScholar, 2025)
One of the biggest annual religious gatherings is the Hajj, which can pose significant health risks for the pilgrims, including overcrowding, filth, and the likelihood of acquiring diseases. Practicing social media is informative and can aid in promoting healthy practices among pilgrims. This study aims to examine the effect of social media on health behaviors during the Hajj using Media System Dependency (MSD). A self-administered questionnaire was distributed to a census sample of 400 pilgrims to assess their utilization of social media for health information. The findings indicate that additional factors such as credibility, usability, and interest in health content influence the pilgrims’ reliance on health-related social media posts. The use of social media following a pilgrimage trip depends upon age and education; older people would search more on social media for health information. Here, we examine social media’s role in public health communication in mass events while offering guidelines to improve health promotion during the Hajj and other international events.
https://openpolicyfinder.jisc.ac.uk/id/publication/29378
Keywords: Salud pública; Medios de comunicación social; Riesgos para la salud - Comunicación; Enfermería - Prevención; Hajj; Public health; Social media; Media reliance theory; Disease prevention; Health communication